1998
DOI: 10.1002/(sici)1521-4141(199805)28:05<1656::aid-immu1656>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of surface antigens recognized by systemic lupus erythematosus antibodies on embryonal cells following differentiation and exposure to corticosteroids

Abstract: We have previously suggested that anti-DNA antibodies present in systemic lupus erythematosus patients can bind directly to tissues as a result of cross-reactivity with embryonal tissue-based antigens. Here we have analyzed the interaction between polyclonal and monoclonal mouse and human lupus autoantibodies and an embryonal cell line. We report that a murine embryonal stem cell line (ES) expresses a surface antigen which is recognized by mouse and human lupus autoantibodies. This surface antigen is down-regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…We previously reported that monoclonal mouse and polyclonal human anti-dsDNA Abs from lupus patients bind to the cell surface of mouse embryonic stem cells. This cell surface receptor was markedly down-regulated by a brief pretreatment of cells with dexamethasone, leading to a Ͼ50% decrease in Ab binding (38). Based on these results, we had postulated that while corticosteroids have many anti-inflammatory and immunosuppressive effects, modulation of target Ag can be invoked as an additional explanation for the therapeutic benefit of steroids in lupus nephritis.…”
Section: Discussionmentioning
confidence: 94%
“…We previously reported that monoclonal mouse and polyclonal human anti-dsDNA Abs from lupus patients bind to the cell surface of mouse embryonic stem cells. This cell surface receptor was markedly down-regulated by a brief pretreatment of cells with dexamethasone, leading to a Ͼ50% decrease in Ab binding (38). Based on these results, we had postulated that while corticosteroids have many anti-inflammatory and immunosuppressive effects, modulation of target Ag can be invoked as an additional explanation for the therapeutic benefit of steroids in lupus nephritis.…”
Section: Discussionmentioning
confidence: 94%
“…23 Other mechanisms include the binding of antibodies found in SLE to membrane antigens on the surface of the embryonal cells. 24 The most important autoantibodies present in SLE are the anti-DNA antibodies, which are found in almost every patient and are of diagnostic importance in SLE. The mechanism by which these autoantibodies leads to the damage observed in lupus patients as well as their effects on reproduction has not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we have demonstrated that monoclonal mouse and polyclonal human anti-dsDNA antibodies bind to the cell surface of undifferentiated mouse embryonic stem cells. 48 However, when these cells are allowed to differentiate, binding is signi cantly reduced. Furthermore, we have shown that a pathogenic anti-dsDNA antibody preferentially binds to glomeruli of BALB = c mice as compared with C57BL = 6 mice.…”
Section: The Cross-reactive Renal Target For Anti-dsdna Antibodiesmentioning
confidence: 99%